1986
DOI: 10.1039/f19868201271
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of inclusion-compound formation for binding of organic dyes, ions and surfactants to α-cyclodextrin studied by kinetic methods based on competition experiments

Abstract: This kinetic and thermodynamic study is concerned with a comparison of binding of simple anions, azo-dyes and longchain surfactants to acyclodextrin. Two competition reactions have been employed. (i) In order to obtain information on the association of simple anions and surfactants with a-cyclodextrin, the competitive binding of an azo-dye with a-cyclodextrin has been used in stopped-flow experiments. (ii) In order to study the binding of the azo-dye pyridine-2-azo-p-dimethylaniline (PADA) to acyclodextrin, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
43
0

Year Published

1988
1988
2011
2011

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(47 citation statements)
references
References 2 publications
4
43
0
Order By: Relevance
“…Clearly, the order of binding with SPFO is P-CD > y-CD > a-CD with the last showing very little association at all. The intersection of the linear portions of the curves for the three cyclodextrins gives the stoichiometry of the main complex formed as 1: 1 in agreement with findings from other surfactant systems (3)(4)(5)(6)(7)(8). All pre-micellar SPFO solutions displayed the same behavior.…”
Section: Resultssupporting
confidence: 76%
See 2 more Smart Citations
“…Clearly, the order of binding with SPFO is P-CD > y-CD > a-CD with the last showing very little association at all. The intersection of the linear portions of the curves for the three cyclodextrins gives the stoichiometry of the main complex formed as 1: 1 in agreement with findings from other surfactant systems (3)(4)(5)(6)(7)(8). All pre-micellar SPFO solutions displayed the same behavior.…”
Section: Resultssupporting
confidence: 76%
“…Recent work has shown that fluorocarbon surfactants bind very strongly with P-CD (2, 3) with little tendency to form inclusates with a-CD (2). However, surfactant hydrocarbon chains of diameter 4.5 A apparently are readily accommodated within the a-CD cavity because stable complexes are formed with both a-CD and P-CD (3)(4)(5)(6)(7)(8). A complicating feature in the hydrocarbon chain situa-.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With aCD, the conductance curves consist of three linear sections, the intersections of which indicate 2:l and 1:l stoichiometric species. The former is more distinct and is the ratio reported by Hersey, Robinson, and Kelly (6). If the first aCD encapsulates the hydrocarbon chain of the surfactant, then the second a C D probably envelopes the polar end in a CD/S/CD complex where S represents the surfactant monomer.…”
Section: Resultsmentioning
confidence: 84%
“…For both weakly and strongly bound drugs, we have attempted to measure the kinetics of this process by various fast kinetics techniques; in no case have we been able to estimate either the "on" or "off" rate-that is, the processes are faster than could be measured. Others have noted values for these kinetics using ultra fast kinetics techniques (Cramer et al, 1967;Rohrbach and Wojcik, 1981;Hersey and Robinson, 1984;Hersey et al, 1986) and have found that in most cases, rates approach those of diffusion-controlled limits. In only one case (unpublished work) did we see some evidence of slow kinetics when we observed nuclear magnetic resonance (NMR) line broadening for a drug with a >1 × 10 5 M -1 binding constant.…”
Section: (3)mentioning
confidence: 99%